2020
DOI: 10.1027/2512-8442/a000042
|View full text |Cite
|
Sign up to set email alerts
|

Fear of Physical Activity, Anxiety, and Depression

Abstract: Abstract. Background: Physical activity (PA) is recommended by heart failure treatment guidelines. Adherence to exercise prescriptions is low and not much is known about everyday PA in this patient group. Aims: This study describes objectively assessed everyday PA/sedentary behavior in men and women with chronic heart failure and examines associations of potential barriers for engaging in PA, namely fear of physical activity (FoPA), general anxiety, and depression, with indicators of PA and sedentary behavior.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 40 publications
0
17
0
Order By: Relevance
“…Within the scope of this study, the patient factors encompass two aspects: namely, high kinesiophobia scores and a low socioeconomic status. Fear of movement is a significant barrier to CR attendance and management in HF patients, which has been confirmed in both qualitative and quantitative studies 25,26 . Moreover, Sina Kianoush et al found that the patients with a higher Social Vulnerability Index exhibited a low utilization rate of CR, who is mainly characterized by poverty, unemployment and educational attainment below high school level in terms of social and economic status 27 .…”
Section: Discussionmentioning
confidence: 90%
“…Within the scope of this study, the patient factors encompass two aspects: namely, high kinesiophobia scores and a low socioeconomic status. Fear of movement is a significant barrier to CR attendance and management in HF patients, which has been confirmed in both qualitative and quantitative studies 25,26 . Moreover, Sina Kianoush et al found that the patients with a higher Social Vulnerability Index exhibited a low utilization rate of CR, who is mainly characterized by poverty, unemployment and educational attainment below high school level in terms of social and economic status 27 .…”
Section: Discussionmentioning
confidence: 90%
“…The 74 articles identified by the systematic review included a total of 13388 participants aged 11 to 85 years, including 7308 women, 4729 men, and 1351 participants whose gender and sex was not reported. The studies investigated populations with pain (n = 37) 62,6471,73,7681,83,88,89,111128 cardiac conditions (n = 6) 86,87,104,129131 , surgery (n = 8) 63,131137 , arthritis (n = 10) 75,82,84,85,91,138142 , neurologic conditions (n = 3) 90,143,144 , pulmonary conditions (n = 3) 145147 , cancer (n = 1) 74 , women health conditions (n = 2) 72,148 , as well as healthy adults (n = 6) 29,85,107,149151 (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Through the Mindful Steps intervention components, participants learned a variety of strategies that were particularly helpful for walking, including breath regulation/ awareness, body awareness, pacing, mind-body exercises, and goal setting. For individuals with COPD and HF, fear of breathlessness or fear of PA (likely due to breathlessness experienced during PA) are barriers to engaging in PA. [59][60][61][62][63] In Mindful Steps, participants practiced breathing exercises (e.g., pursed lip breathing) and learned how to nonjudgmentally attend to their breath. At 6-months, we identified prominent themes regarding the usefulness of the breathing exercises and improvements in breathing.…”
Section: Discussionmentioning
confidence: 99%